DISTRIBUTOR SALES APPLICATIONS IN MOTOR SHOP SPAREPART PANDROLTECH USING PHP & MY SQL - Melya Novita; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2008)
This explains the scientific writing about the creation of dynamic web based applications penjulan online as a medium or media commerce over the Internet using PHP and MySQL. Making web-based application is intended to help enable customers to shop in motor spare parts ordering transaction at this Pandroltech store. To complete the creation of this web-based applications using literature studies, both authors of books or the Internet as a reference and comparison.  Ease of transactions via the Internet  is possible because of the dynamic web-based programming is very supportive of the sale transaction.